Improving phi -OTDR Signal-to-Noise Ratio to Reduce Ambiguity in Intrusion Detection - Yusri M.S.; Faisal B.; Ismail M.F.; Nordin N.D.; Saleh N.L.; Ismail A.; Abdullah F.; Jamaludin M.Z.; Sulaiman A.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electromagnetic pulse; Rayleigh scattering; Signal to noise ratio; Time domain analysis; Acoustic sensing; Compact size; Condition; Distributed acoustic sensing; Fiber-optics; Intrusion-Detection; Optical time domain reflectometry; Perimeter intrusion detection; Perimeter intrusion detection systems; Phase optical time domain reflectometry; Intrusion detection